Software evaluation on infant development to support teaching and professional training* - Wesley Soares de Melo; Hévila Ferreira Gomes Medeiros Braga; Maria Vera Lúcia Moreira Leitão Cardoso; Emanuella Silva Joventino Melo; Flávia Paula Magalhães Monteiro (Universidade de São Paulo, 2024)
Abstract Objective: evaluate the functional performance and technical quality of the Wise Infant Development® educational software with experts. Method: methodological research that followed the software evaluation process according to the ISO/IEC 25010 and NBR ISO-IEC 14598-6 standards. The software's functional performance was assessed by a group of nurse experts and its technical quality by information technology experts. The Content Validity Index and the Binomial test were used for statistical analysis. Results: in both expert groups, agreement was greater than 70%, indicating that the software is suitable and pertinent to what was proposed in all its evaluated characteristics: functional suitability, reliability, usability, performance efficiency, compatibility, security, maintainability, and portability. The technology received suggestions for improvement, which were accepted. Conclusion: the Wise Infant Development® software was well evaluated by the experts and could contribute to teaching about infant development, both in undergraduate nursing courses and in professional training.